2004
DOI: 10.1182/blood-2003-12-4365
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of intravascular thrombosis in murine endotoxemia by targeted expression of hirudin and tissue factor pathway inhibitor analogs to activated endothelium

Abstract: We have generated transgenic mice expressing the leech anticoagulant hirudin and human tissue factor pathway inhibitor tethered to the cell surface by fusion with fragments of human CD4 and P-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 28 publications
3
56
1
Order By: Relevance
“…Results from complimentary but distinct experimental approaches, using either WT or PAR-1 KO hearts transplanted into defi binogenated rats or CD31-Hir-Tg hearts transplanted Thrombin generation during systemic infl ammation is highly dependent on the procoagulant changes induced on endothelium ( 26 ). Why mammals have evolved or maintained, as an integral part of EC activation, the switch from an anticoagulant to a procoagulant phenotype is interesting because if it results in intravascular thrombosis it can pose a direct threat to the survival of the individual, as often occurs during acute severe sepsis.…”
Section: Brief Definitive Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from complimentary but distinct experimental approaches, using either WT or PAR-1 KO hearts transplanted into defi binogenated rats or CD31-Hir-Tg hearts transplanted Thrombin generation during systemic infl ammation is highly dependent on the procoagulant changes induced on endothelium ( 26 ). Why mammals have evolved or maintained, as an integral part of EC activation, the switch from an anticoagulant to a procoagulant phenotype is interesting because if it results in intravascular thrombosis it can pose a direct threat to the survival of the individual, as often occurs during acute severe sepsis.…”
Section: Brief Definitive Reportmentioning
confidence: 99%
“…Cell culture. Mouse microvascular ECs were purifi ed and passaged as described previously ( 26 ) and used at passages 1 -3.…”
Section: Animalsmentioning
confidence: 99%
“…It has been recently reported that platelets accumulate in the livers and lungs of LPS-treated animals. 21 In Figure 5B-C, platelet accumulation is clearly shown in ␤-gal stained livers, lungs, and spleens, but only in mice under Tet-off conditions. No significant platelet accumulation in the above tissues was observed in mice that were not treated with LPS compared with LPS-treated mice (data not shown).…”
Section: Inducible Expression Of ␤-Galactosidase and Generation Of A mentioning
confidence: 90%
“…Double-transgenic mice were anaesthetized with isoflurane (40 g/g body weight) and intraperitoneally injected with lipopolysaccharide (LPS) (E coli serotype 0127;B8; Sigma), at a dosage of 60 g/g of body weight, or saline in a total volume of up to 100 L (control), essentially as described in Chen et al 21 Mice were killed 2 hours after LPS or saline administration and perfused for 5 minutes with 1 ϫ PBS, followed by 2% paraformaldeldyde for 15 minutes and, finally, 1 ϫ PBS for 10 minutes. The livers and lungs were surgically removed immediately after fixation and subjected to staining for ␤-galactosidase as described above.…”
Section: Lps-induced Acute Inflammation and Tissue Sectionsmentioning
confidence: 99%
“…Targeting coagulation cascade proteins could be an effective way to modulate inflammation. Indeed, A. Dorling from Imperial College London showed that targeted expression of the anticoagulants hirudin and tissue factor pathway inhibitor effectively inhibited intravascular thrombosis in a model of murine endotoxemia and markedly inhibited vascular remodeling after injury [30]. In addition to hirudin and tissue factor, the ubiquitous stress-responsive gene heme oxygenase-1 (HO-1) and carbon monoxide (CO) also control inflammatory responses.…”
Section: Alternative Targets and New Trends For Immunosuppressionmentioning
confidence: 99%